Political Morality in Modern Governance: Between Ethics, Power, and Public Interest - Luis Armando Sabarofek; Zuly Qodir (International Journal of Social Science and Business, 2026)
This paper discusses political morality in modern government by highlighting the relationship between public ethics, the exercise of power, and the public interest. The purpose of this study is to analyse the position of political morality in government practice and to explain how the dimensions of morality, ethics, and power influence each other in shaping the legitimacy of government. The research uses a qualitative approach through indexed literature reviews and content analysis of national media news. The data were analysed using NVivo 12 Plus through thematic coding techniques, concept map visualisation, and. The results show that political morality in modern government is reflected in three main dimensions: the morality of elite behaviour, institutional morality, and public policy morality. Media findings broadcast patterns of ethical deviations, secrecy of power, and recurring moral legitimacy crises, especially when institutional accountability and transparency weaken. This study also found that political morality functions as an evaluative basis for the quality of power, as affirmed by Weber's theory of legitimacy, Rawls' justice, and Habermas' communication ethics. In conclusion, political morality is the main foundation for strengthening the legitimacy of power and public trust. This paper offers a conceptual model of the relationship between morality, ethics, and power as a new contribution to governance studies. Future research should expand empirical analysis at the local level and develop more operational indicators for evaluating political morality.